The Mental Health Policies in Western Countries - Douki, Stamatina; Kelesi-Stavropoulou, Martha (HAPSc Policy Briefs Series, 2022)
Although mental health is difficult to be defined interculturally, nevertheless, it is related not just to the absence of a disease but to the ability of the individual to be functional and satisfied. Mental diseases are usually chronic and they bring about a significant degree of disability while they require high treatment costs. The aim of this study is to investigate and present mental health management policies in western countries. The methodology followed includes literature review of relevant publications collected through Google Scholar, Pubmed online databases, as well as through articles, journals and doctoral theses. From the thorough analysis of the international and Greek literature it appears that there is a revision of the way of care/management of the mental care, the development of a Network of Mental Health Services in the Community, the creation of a Network to defend the rights of the mentally ill, a definitive abolition of large psychiatric hospitals in several countries in the west, as well as a reconstruction of buildings and significant reduction of beds in large psychiatric hospitals. The study of the international literature makes it clear that mental health reform efforts are necessary internationally and in Greece but need to be redefined in times of socioeconomic upheaval.